PENERAPAN METODE PEMBELAJARAN PROBLEM SOLVING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI KOLOID KELAS XI IPA SMA NEGERI 4 BANJARMASIN - Salwa Yustina; Yudha Irhasyuarna; Muhammad Kusasi (Universitas Lambung Mangkurat, 2015)
Abstract: A research on the application of the learning methods of problem solving in the colloidal material class XI Science SMAN 4 Banjarmasin. This study aims to determine (1) differences in critical thinking skills students learn to use problem solving methods with conventional learning, (2) a response to the problem solving method in class XI IPA. Methods This study used a pretest- posttest nonequivalent control group design. Research sample is class XI Science SMAN 4 Banjarmasin which consists of class XI IPA 3 as the experimental class and class XI Science 2 as the control class. Data collection techniques using critical thinking skills tests and questionnaires. Statistical analysis using t-test, test for normality and homogeneity tests. The results showed that (1) there is a difference between the critical thinking skills that students learn to use problem solving methods with students who learn using conventional learning methods, namely the experimental class and 74.8% in the control class is 70.41% (2) response to learning of problem solving methods are categorized both by 32.2%.Keywords: problem solving, critical thinking skills, colloidal